Al Jazeera, freedom of the press, and forecasting humanitarian emergencies - Ghanem, Yehia (New York, NY : Routledge, 2021)
"This book reveals how Al Jazeera and its news coverage became a force for change politically, socially and culturally in the Middle East in general, and the Arab World in particular. It explores pre-Al Jazeera and post-Al Jazeera representations of humanitarian crises and identifies a potentially significant partnership between the news organizations and humanitarian actors. By tracing the evolution of the news network, the book sheds new light on how Al Jazeera effected change in the Global South. The research identifies a significant relationship between Al Jazeera's news coverage and the ability to forecast international humanitarian actions, politically and militarily. It also explores the potential for continued partnership between humanitarian actors and news organization to identify crises in their early stages. Lastly, the book examines the distinct, original lexicon developed by Al Jazeera for humanitarian affairs and shows how the network influenced international media stylebooks and changed humanitarian coverage on key global issues. A compelling examination of Al Jazeera's news operation that will be of interest to students and scholars of Media Studies, Political Communication, Journalism and News Reporting, International Politics and the Media, and Arab Media"--
"Routledge Focus" -- taken from front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Al Jazeera (Television network); Television broadcasting of news -- Middle East; Humanitarianism -- Press coverage -- Middle East; Humanitarian assistance -- Press coverage -- Middle East; Disasters -- Press coverage -- Middle East; Disaster relief -- Press coverage -- Middle East; Freedom of the press -- Middle East; Journalistic ethics -- Middle East; SOCIAL SCIENCE / Media Studies